2002
DOI: 10.1016/s0002-9440(10)64929-2
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline Modulates Smooth Muscle Cell Growth, Migration, and Matrix Remodeling after Arterial Injury

Abstract: The tetracyclines function as antibiotics by inhibiting bacterial protein synthesis, but recent work has shown that they are pluripotent drugs that affect many mammalian cell functions including proliferation, migration, apoptosis, and matrix remodeling. Because all of these processes have been implicated in arterial intimal lesion development, the objective of these studies was to examine the effect of doxycycline treatment using a well-characterized model of neointimal thickening, balloon catheter denudation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
127
1
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(141 citation statements)
references
References 42 publications
(47 reference statements)
7
127
1
6
Order By: Relevance
“…This is in line with studies showing prevention of blood flow-induced artery enlargement 31 and inhibition of several phases of intimal thickening after arterial injury. 32 In contrast to results obtained in large arteries, doxycycline treatment did not modify vascular remodeling in mesenteric arteries, suggesting that despite the increase of MMP-2 activity, this family of enzymes does not appear to be necessary for the eutrophic remodeling process to occur. Interestingly, doxycycline appeared to influence small artery "hypertrophy," although it is not a main feature in this model.…”
Section: Bouvet Et Al Matrix Changes During Eutrophic Remodelingmentioning
confidence: 56%
“…This is in line with studies showing prevention of blood flow-induced artery enlargement 31 and inhibition of several phases of intimal thickening after arterial injury. 32 In contrast to results obtained in large arteries, doxycycline treatment did not modify vascular remodeling in mesenteric arteries, suggesting that despite the increase of MMP-2 activity, this family of enzymes does not appear to be necessary for the eutrophic remodeling process to occur. Interestingly, doxycycline appeared to influence small artery "hypertrophy," although it is not a main feature in this model.…”
Section: Bouvet Et Al Matrix Changes During Eutrophic Remodelingmentioning
confidence: 56%
“…15,24,27,36,91 MMP-9 inhibitors have showed utility in protection from ICH. [92][93][94] Inhibiting MMP-9 may also negate the harmful effects of AVMrelated inflammatory responses. Lee et al 28,29 evaluated the effect of the MMP-9 inhibitors minocycline and pyrrolidine dithiocarbamate on an AVM mouse model and showed that MMP-9 blockade significantly reduced the extent of hemorrhage.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…Balloon angioplasty was performed as previously described. 31 After balloon injury, an intra-arterial bolus of 200-g CRP was injected through the same entrance at left external artery by a silicon tube, detained for 1 minute, and followed by an injection of 1-mL low-temperature gelling agarose (Type VII, Sigma) mixed with CRP at a concentration of 100 g/mL around the carotid artery. 32 In a subgroup, losartan in the drinking water (15 mg/kg per day) was started 3 days before balloon angioplasty and continued to the end of experiment.…”
Section: Carotid Artery Balloon Angioplasty Modelmentioning
confidence: 99%
“…Rats were euthanized at various time points after injury, chosen as follows on the basis of previous studies elucidating the kinetics of the injury response. 31 Cross-sectional rings (4 mol/L) were cut at 5 mm before the bifurcation of internal and external carotid arteries and stained with hematoxylin and eosin, Trichromes stain, smooth muscle cell ␣-actin (DAKO), 5-bromo-2Ј-deoxyuridine (BrdU, DAKO), Picro-Sirius Red (for collagen staining, measured by confocal microscope), AT 1 -R, CD45, histone H1, and monocyte and macrophage. Smooth muscle cell proliferation was measured in the media and intima with 100 mg of BrdU injected intraperitoneally 24 hours before sacrifice.…”
Section: Carotid Artery Balloon Angioplasty Modelmentioning
confidence: 99%